Social Inequality and Academic Achievement Trajectories of Schoolchildren in the City of Córdoba, Argentina (Itinerarios Educativos, 2020)
In a context of poverty but with a high schooling rate, this work is intended to elucidate if children inCórdoba, Argentina, show differences in their academicachievement (AA) trajectories associated with socioeconomic characteristics. A prospective cohort study wasconducted with schoolchildren, in which annual measurements of AA and baseline measurements of socialcharacteristics were collected: sex, mother’s educationallevel, parental occupational stratum, socioeconomiclevel (SEL) and intellectual capacity (IC). Four categorieswere defined for academic achievement trajectoriesaccording to their scores obtained in the subjects of Language and Mathematics at the beginning and end of theconducted analysis, and in relation to their promotionor not to the next grade by the end of each school year.The four categories for trajectories were: distinguished,satisfactory, regular, and unsatisfactory. Binomial andmultinomial logistic regression models were used toexamine the presence of social inequalities. Significant differences were found in academic achievementtrajectories depending on the studied socioeconomicvariables, whose effects were not independent of theintellectual capacity. Intellectual capacity was stronglyassociated with mother’s educational level, parentaloccupational stratum, and SEL. The influence of socialinequalities on intellectual capacity and academicachievement trajectory was proved.
Keywords: social inequalities; academic performance; trajectories; childhood; primary school